Strategi Pemasaran Dalam Meningkatkan Jumlah Anggota Simpanan Wadiah Pada USPPS BMT Sunan Drajat Tunggul Paciran Lamongan - Siti Nur Aini; Rachma Indrarini (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
USPPS BMT Sunan Drajat has several strategies so that the number of Wadi'ah Savings members experiences a significant increase every year. The purpose of this study was to determine whether the strategy implemented by USPPS BMT Sunan Drajat could increase the number of Wadi'ah Savings members. The research subjects were taken using the purposive sampling method and the data sources were obtained through interviews. The validity test is done by the triangulation technique. The results of this study indicate that the marketing strategy applied by USPPS BMT Sunan Drajat on Wadi'ah Savings products is to use the Segmenting, Targeting, Positioning marketing method. Segments are selected based on occupation. The selected targets are entrepreneurs. BMT to attract public interest and trust through the image of Pondok Pentren Sunan Drajat. BMT Sunan Drajat also implements a Marketing Mix strategy which consists of Product Strategy, Price Strategy, Place Strategy, and Promotion Strategy.